Perilaku Anggota Keluarga Terhadap Kegiatan Penanggulangan Masalah Sampah Rumah Tangga - Hadiyanti, Puji (Journal of Nonformal Education and Community Empowerment, 2021)
This research aims to find out response of family and community members to existing businesses or activities, how to change the social behavior of familymembers and the community towards a business or existing activities. Thisresearch is a continuation of previous research where the results of the research arein the form of a social action model for tackling the waste problem. The socialaction in question is carried out through a community education process in theform of waste recycling training for the community of Way Huwi village.Through the training process, it is hoped that behavior changes will occur not onlyfrom an economic perspective but also from a social and environmentalperspective, so that the purpose of the training is achieved, namely a change inbehavior towards waste problems. This research was conducted through aqualitative approach. The results of this study indicate that there is a change inbehavior and a good assessment of the Way Huwi village community towardstackling household waste problems. The form of behavior change referred to isfrom being indifferent or disgusted by waste to caring and being able to carry outactivities to tackle the waste problem.